2021
DOI: 10.1111/cod.13842
|View full text |Cite
|
Sign up to set email alerts
|

Patch test results in terms of the recently recommended allergens in children and adolescents: A retrospective cohort study over 22 years from Turkey

Abstract: BackgroundA European pediatric patch test series was suggested recently.ObjectivesTo evaluate the patch test results in children (<10‐years‐old) and adolescents (10‐ to 18‐years‐old) in Turkey, focusing on the clinical/occupational relevance and the diagnostic value of the recently suggested series.Patients and MethodsA retrospective cohort study on 317 consecutively patch tested patients ≤18 years of age, between 1996 and 2017.ResultsThe contact sensitization rate was 46.1%. Allergic contact dermatitis (AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 53 publications
4
14
0
Order By: Relevance
“…The largest increase was observed for MI. A sensitization prevalence of 1.9% to 6% for MCI/MI has been described in other studies, including paediatric patients 2,11–13,15,21 . MCI and MI have been widely used as preservatives in care products for children, such as baby wipes, creams, shampoos and moisturizers 25 .…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…The largest increase was observed for MI. A sensitization prevalence of 1.9% to 6% for MCI/MI has been described in other studies, including paediatric patients 2,11–13,15,21 . MCI and MI have been widely used as preservatives in care products for children, such as baby wipes, creams, shampoos and moisturizers 25 .…”
Section: Discussionmentioning
confidence: 74%
“…The present study found that 20.3% of patients would have been underdiagnosed if tested with the EBS only. Turkish researchers have found the diagnosis of ACD would have been missed in more than one fourth of the children if not tested with additional series and the patient's own material 21 . Similarly, of 883 children patch tested by the North American Contact Dermatitis Group, 23.6% had a relevant positive reaction to allergens not included in the standard screening panels 6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Studies from Turkey report that contact sensitization rates in the pediatric population are 32%-57%. 8,9 In our study, we established that the contact sensitization rate in the Turkish pediatric population is 18.8%. The small percentage in our study compared with others in Turkey might be due to the fact that we only used European baseline series allergens in our patch test.…”
Section: Discussionmentioning
confidence: 72%